Antara Eksplorasi dan Konservasi: Pendekatan HAM dalam Tanggung Jawab Negara terhadap Kerusakan Laut sebagai Pelanggaran HAM - Javier Maramba Pandin (Jurnal Hukum Lex Generalis, 2026)
This article examines state responsibility for marine degradation as human rights violation through a Human Rights-Based Approach. Utilizing normative research method that combine multiples approaches, the article argues that marine pollution is not human rights violations, but inherently constitutes a violation of the rights to health, food and a healthy environment. Through the elaboration of the concept of the right to environment at sea on state responsibility under human rights obligations, this article concludes that the transformation from a monitoring model based on voluntary corporate compliance to an obligationbased model is a legal obligation, rather than a mere choice.